Effects of Small-Sided Game Variation on Changes in Hamstring Strength. Issue 3 (March 2019) - Madison, Glenn; Patterson, Stephen David; Read, Paul; Howe, Louis; Waldron, Mark
Abstract : Abstract: Madison, G, Patterson, SD, Read, P, Howe, L, and Waldron, M. Effects of small-sided game variation on changes in hamstring strength. J Strength Cond Res 33(3): 839–845, 2019—Small-sided games (SSGs) are commonly used by soccer practitioners to condition players. This form of exercise can result in fatigue, potentially exposing the muscle to injury risk. The purpose of this study was to determine the effects of SSG variations on hamstring torque in semiprofessional soccer players. In a counterbalanced cross-over design, 10 male semiprofessional soccer players took part in both small relative area (3 vs. 3; 300 m 2 ) and large relative area (4 vs. 4; 1000 m 2 ) SSGs. The games comprised 6 × 4-minute bouts, with 90-second recovery. Both movement and heart rate responses were monitored by global positioning systems (GPS) and hamstring isometric torque was measured pre-training and post-training using a NordBord. There were differences ( p < 0.05) between the small and large relative area games for peak hamstring force decrement (5.78 N and −13.62 N, respectively) and mean hamstring force decrement at 90° (11.11 N and −4.78 N, respectively). The number of accelerations was related to ( r = 0.46, p = 0.039) reduced hamstring peak torque at 90°. In conclusion, larger relative area SSGs elicited the greatest internal and external loads, resulting in decrements in hamstring force. The number of accelerations performed in the session increases the likelihood of hamstring fatigue and can be controlled with the relative pitch area.